Fundamentals of electric power engineering : from electromagnetics to power systems - Ceraolo, Massimo; Poli, Davide (Hoboken, New Jersey : IEEE Press, John Wiley & Sons, 2014)
"At the basis of many sectors of engineering, electrical engineering deals with electricity phenomena involved in the transfer of energy and power. Professionals requiring a refresher course in this interdisciplinary branch need look no further than Fundamentals of Electric Power Engineering, which imparts tools and trade tricks to remembering basic concepts and grasping new developments. Even established engineers must supplement their careers with an invigorated knowledge base, and this comprehensive resource helps non-electrical engineers amass power system information quickly"--
"Covers topics such as: circuits, electrical machines and drives, power electronics, power system basics. new generation technologies"--
Preliminary Material -- Electric Circuit Concept and Analysis -- Electric Machines and Static Converters -- Power Systems Basics -- Appendix: Transmission Line Modelling and Port-Based Circuits.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Electric power systems; TECHNOLOGY & ENGINEERING / Electronics / General; Electric power systems; Electronic books; Electronic books